Cuticular wax biosynthesis as a way of inducing drought resistance - Seo, Pil Joon (Landes Bioscience, 2011)
Plants have evolved diverse adaptive strategies to cope with drought or water deficit conditions, such as stomatal closure, maintenance of root growth and water uptake, and biosynthesis of osmoprotectants. Accumulation of cuticular waxes also contributes to drought resistance. However, it is still unclear how cuticular wax biosynthesis is regulated in response to drought and how it is associated with plant responses to drought at the molecular level. The abscisic acid (ABA)-inducible MYB96 transcription factor plays a role in drought resistance. Notably, it also regulates cuticular wax biosynthesis by binding directly to the promoters of genes encoding fatty acid elongating enzymes, such as KCS, KCR and ECR that constitute a rate-limiting step in cuticular wax biosynthesis. In the myb96-1D mutant that constitutively express the MYB96 gene, many of genes involved in cuticular wax biosynthesis are upregulated and accordingly, cuticular wax accumulation is greatly elevated. In contrast, cuticular wax accumulation is reduced in the myb96-1 mutant, linking drought with cuticular wax biosynthesis. It is evident that the MYB96 transcription factor incorporates drought stress signals into a gene regulatory network that modulates cuticular wax biosynthesis under drought stress conditions, providing a first molecular mechanism by which cuticular wax biosynthesis contributes to drought resistance and protection from pathogenic and mechanical damages as well.